INTEGRASI SLIMS PERPUSTAKAAN BADAN PPSDM KESEHATAN MENUJU KINK (KATALOG INDUK NASIONAL KESEHATAN) KEMENKES RI DAN INDONESIA ONE SEARCH - Nadia Amelia Qurrota A'yunin; Dwi Fajar Saputra (Perpustakaan Nasional RI, 2017)
The research entitled Integration of SliMs Library of PPSOM Health Agency towards KINK (National Main Catalog of Health) Ministry of Health RI and Indonesia OneSearch aimed to know the process of integration of SliMs Library of PPSDM Health Agency to KINK Ministry of Health RI and Indonesia OneSearch, and to know the obstacles in the integration process of SliMs Library PPSOM Health Agency to KINK Ministry of Health RI and Indonesia OneSearch. The research used qualitative descriptive method. The data were collected by direct observation in the Library of PPSDM Health Agency, Ministry of Health RI. The integration process of SliMs Library of PPSDM Health Agency to KINK Kemenkes RI and Indonesia OneSearch begins with: 1) The process of data conversion from library information system. 2) Adjustment to table format in SUMS database based on Anglo American Catalouging Rules II (AACR II) standard. 3) Storage of adjustment of biblio table and items with excel format Comma Separated Values (CSV) type. Then the conversion process was performed by importing data into the SUMS database by utilizing import item feature and import data; the biblio table was stored in the import data while the item table was stored in the import items. 4) After the conversion process using import feature successfully done, then do recheck at SUMS. Examination can include some parts of the feature bibliographic list, item list and OPAC. 5) The final stage of the integration process was to store connecting devices on the SUMS server. 6) The integration process was successful and indexed in KINK and Indonesia OneSearch. While, the obstacles in the process of integration SliMs Library of PPSDM Health Agency to KINK Ministry of Health RI and Indonesia OneSearch include: 1) Incomplete initial database for data conversion, 2 Slow coordination between work units.